Validation of the Kaba Volcanic Eruption Disaster Mitigation E-Module as a Learning Media on Volcano Materials - Purwaningsih; Johan, Henny; Mayub, Afrizal (Kasuari: Physics Education Journal (KPEJ), 2025)
Indonesia is on the path of the "Pacific Ring of Fire," so it has a high risk of catastrophic volcanic eruptions. One of the active volcanoes that has the potential to have a big impact is Mount Kaba. To improve students' understanding of disaster mitigation, this study aims to develop and validate a science learning e-module about volcanoes that is integrated with the disaster mitigation of the eruption of Mount Kaba. This study uses a qualitative descriptive method with a 4D model Research and Development (R&D) approach, which consists of the Define, Design, Develop, and Disseminate stages, but only carried out until the development stage, namely validation. Data was collected through observations, questionnaires, and interviews involving teachers and validators from among disaster mitigation and science education experts. The validation results show that the e-module obtained an average score of 92% with the category "Very Feasible" based on the feasibility of content, language, and graphic display. These results indicate that the e-module has great potential as a learning medium for disaster mitigation in schools.